2018
DOI: 10.1016/j.ymeth.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Separation of neural stem cells by whole cell membrane capacitance using dielectrophoresis

Abstract: Whole cell membrane capacitance is an electrophysiological property of the plasma membrane that serves as a biomarker for stem cell fate potential. Neural stem and progenitor cells (NSPCs) that differ in ability to form neurons or astrocytes are distinguished by membrane capacitance measured by dielectrophoresis (DEP). Differences in membrane capacitance are sufficient to enable the enrichment of neuron- or astrocyte-forming cells by DEP, showing the separation of stem cells on the basis of fate potential by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 37 publications
(81 reference statements)
0
35
0
Order By: Relevance
“…The separation of neuron and astrocyte progenitors is crucial to improve the purity of transplanted stem cells in clinical therapy. Adams et al demonstrated that these subpopulations could be effectively separated by the alternate current (AC) DEP due to the different electrophysiological properties of the cell membranes (whole-cell membrane capacitance) revealing at a certain stage of the cell differentiation [204]. Previously, El-Badawy et al examined the electrophysiological properties of adipose stem cells (ASCs) and bone-marrow mesenchymal stromal cells (BM-MSCs) with AC DEP [205].…”
Section: Electrokinetic Cell Separationmentioning
confidence: 99%
“…The separation of neuron and astrocyte progenitors is crucial to improve the purity of transplanted stem cells in clinical therapy. Adams et al demonstrated that these subpopulations could be effectively separated by the alternate current (AC) DEP due to the different electrophysiological properties of the cell membranes (whole-cell membrane capacitance) revealing at a certain stage of the cell differentiation [204]. Previously, El-Badawy et al examined the electrophysiological properties of adipose stem cells (ASCs) and bone-marrow mesenchymal stromal cells (BM-MSCs) with AC DEP [205].…”
Section: Electrokinetic Cell Separationmentioning
confidence: 99%
“…However, it is a reasonable method for many applications. For instance, it can be used for particle sorting methods such as acoustophoresis and dielectrophoresis in which the channel size is usually larger than 100 μm [12]- [14]. In addition, it is needed to be taken into account that printed molds can be used several times.…”
Section: -5mentioning
confidence: 99%
“…Hollow circular images are used for targeted CTC trapping, while long rectangular light bar is used to attract other untargeted cells. Adams et al [21] perform sorting of neural stem and progenitor cells using microfluidic DEP device. The sorting is based on the cell membrane capacitance variation, which specifically determines the future forming cells, either neuron or astrocyte.…”
Section: Dielectrophoretic Manipulation Of Bioparticlesmentioning
confidence: 99%